2014
DOI: 10.1063/1.4874795
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of the effect of the irradiation temperature on the behavior of cubic zirconia

Abstract: High-temperature stability of ion-implanted zirconia and spinel J. Appl. Phys. 97, 113509 (2005) ) and at five temperatures: 80, 300, 573, 773, and 1073 K. Irradiated samples have been characterized by Rutherford backscattering spectroscopy in channeling mode, X-ray diffraction and transmission electron microscopy techniques in order to determine the disordering kinetics. All experimental results show that, whatever is the irradiation temperature, the damage build-up follows a multi-step process. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
7
31
0
Order By: Relevance
“…1. Damage profiles at this cryogenic temperature appear similar to those obtained at higher temperatures [30]. The fact that the fluence ($10 15 cm À2 ) at which the disorder level significantly increases is the same as that for crystals subjected to room-temperature irradiation indicates that defect mobility is identical at both temperatures.…”
Section: Rutherford Backscattering Spectrometrysupporting
confidence: 69%
See 2 more Smart Citations
“…1. Damage profiles at this cryogenic temperature appear similar to those obtained at higher temperatures [30]. The fact that the fluence ($10 15 cm À2 ) at which the disorder level significantly increases is the same as that for crystals subjected to room-temperature irradiation indicates that defect mobility is identical at both temperatures.…”
Section: Rutherford Backscattering Spectrometrysupporting
confidence: 69%
“…Two main advanced techniques, HRXRD and SAXS that both combine state-of-the-art experimentation and simulation approaches, have clearly demonstrated their potential in this field. HRXRD can be employed to measure the strain in strainengineered materials for enhanced physical properties [46,47], and to examine correlation between strain/stress and disorder in materials subjected to ion irradiation [30,48]. SAXS allows characterization of density changes on the nanoscale associated with irradiation-induced microstructural transformations, such as formation of extended defect [50], modification of nanoparticle shape [49,51], and creation of ion tracks [23,52].…”
Section: X-ray Based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the values of Ed vary with sublattice of cations and anions, experimental measurements of Ed in ceramics are relatively difficult than metals [11,12]. For this reason, reported values of Ed of O and Zr sublattices in cubic zirconia are limited and vary within a certain range, thereby, it had been assumed that values Ed of O and Zr sublattices are in the range of 20-40 and 50-80 eV, respectively [13,14]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Debelle et al [13] showed in 4 MeV Au 2+ irradiated YSZ that there is a significant variation of the threshold fluence for initiating the damage step with irradiation temperature, although the disorder level at high fluence is similar, irrespective of temperature. The transition fluence to step 2, which is the fluence where the accumulated damage in RBS/C experiments revealed a steep increase, decreased with increasing irradiation temperature [13]. This suggests that the lattice disordering proceed relatively at lower fluence at higher temperature irradiation.…”
Section: (A) (B) (A) (B)mentioning
confidence: 99%